Altered medial temporal lobe subregion volumes in systemic lupus erythematosus patients with neuropsychiatric symptoms - Z. Makdad Najeeb; P. C. Sundgren; A. Jönsen; K. Zervides; J. Lätt; T. Salomonsson; J. Nystedt; P. Nilsson; A. Bengtsson; G. Kuchcinski; L. E. M. Wisse (BMC Rheumatology)
Abstract Background Systemic lupus erythematosus (SLE) often presents with neuropsychiatric (NP) involvement, including cognitive impairment and depression. Past magnetic resonance imaging (MRI) research in SLE patients showed smaller hippocampal volumes but did not investigate other medial temporal lobe (MTL) regions. Our study aims to compare MTL subregional volumes in SLE patients to healthy individuals (HI) and explore MTL subregional volumes in relation to neuropsychiatric SLE (NPSLE) manifestations. Methods A total of 70 SLE patients and 25 HI underwent clinical evaluation, cognitive testing, and 3 tesla MRI imaging. T1-weighted MRI images were analyzed using the Automatic Segmentation of Hippocampal Subfields-T1 software. Analyses of Covariance were used to compare MTL subregion volumes between SLE and HI, and between NPSLE and non-NPSLE patients according to three models: the American College of Rheumatology (ACR) model defined by the ACR case definitions for NPSLE (n = 42), the more stringent Systemic Lupus International Collaborating Clinics (SLICC) B model (n = 21), and the most stringent SLICC A model (n = 15). Additionally, we explored the relation between MTL subregion volumes, cognitive functions, and depression scores in SLE patients using partial correlation analyses. Results Significantly smaller volumes of bilateral whole hippocampus, anterior hippocampus, posterior hippocampus, and Brodmann Area 35 were demonstrated in NPSLE compared to non-NPSLE patients according to the ACR model (p = 0.01, p = 0.03, p = 0.04, and p = 0.01 respectively). The differences did not reach significance according to the SLICC B and SLICC A models. No significant differences in MTL subregional volumes between SLE patients and HI were found. Partial correlation analyses showed a significant positive correlation between left Brodmann Area 35 volume and complex attention scores in SLE patients. No significant associations between MTL subregion volumes and depression scores were demonstrated. Conclusions NPSLE patients display significantly smaller volumes in various subregions of the MTL compared to non-NPSLE patients. These findings are suggestive of neuronal damage in MTL subregions in NPSLE patients on a group level.